Trends in leisure time physical activity, smoking, body mass index and alcohol consumption in Danish adults with and without diabetes: A repeat cross-sectional national survey covering the years 2000 to 2010 - Molsted, Stig; Johnsen, Nina Føns; Snorgaard, Ole (Diabetes research and clinical practice, 2014)
In recent decades there has been an increased focus on non-pharmacological treatment of diabetes. The aim of this study was to investigate trends in leisure time physical activity (PA), smoking, body mass index (BMI), and alcohol consumption reported in 2000, 2005 and 2010 by Danish subjects with diabetes. Data comprised level of leisure time PA (inactive; moderate active; medium active; high active); smoking; BMI; and alcohol consumption, provided by The Danish Health and Morbidity Surveys. Participants older than 45 years with or without diabetes were included from cross-sectional analyses from 2000, 2005 and 2010. In participants with diabetes, leisure time PA levels increased from 2000 to 2010: The percentage of those that were physically active increased from 53.5% to 78.2% (p<0.001; women) and from 67.8% to 79.1% (p=0.01; men). The prevalence of daily smokers was reduced from 27.2% to 16.4%, p=0.015, in women with diabetes. In men with diabetes, BMI increased from 27.2±4.0 to 28.6±5.1kgm−2, p=0.003, and men who exceeded the maximum recommendation for alcohol consumption increased from 9.4% to 19.0%, p=0.007. The leisure time PA level was reduced in participants with diabetes compared to participants without diabetes throughout the study. The percentage of physically active Danish participants older than 45 years with diabetes increased from 2000 to 2010, and the most beneficial trends in life style were observed among the women. These trends may have serious implications for cardiovascular risk in Danish patients with diabetes.